FOR A FREE LISTENING - Roberto Kittel Pohlmann; José Estevan Gava (Editora da Universidade de Santa Cruz do Sul, 2014)
This article discusses the free music listening, which promotes musical knowledge and listening to the widest range of music, releasing the listener, even if partially, with respect to musical repertoires publicized and praised by the mass communication media. As a theoretical foundation and starting point are considered here the works of Murray Schafer about ear cleaning and Gaston Bachelard about the notion of habit. From these authors in particular and teaching experiences reported here, are summed up here techniques and strategies to implement and encourage alternative forms of freer and mindful music listening.